2014
DOI: 10.3345/kjp.2014.57.3.125
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of Fanconi anemia: clinical manifestation and treatment outcome

Abstract: PurposeThe aim of this study was to characterize Korean patients with Fanconi anemia (FA), which is a rare but very challenging genetic disease.MethodsThe medical records of 12 FA patients diagnosed at Chonnam National University Hospital from 1991 to 2012 were retrospectively reviewed.ResultsThe median age at diagnosis was 6.2 years. All patients showed evidence of marrow failure and one or more physical stigmata. Chromosome breakage tests were positive in 9 out of 11 available patients. The median follow-up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
2
9
2
Order By: Relevance
“…Eye dysmorphism was present in half of the patients, a rate higher than that reported by Dokal 15 and Shimamura et al 1 as well as that reported from Korea. 11 The rate of hearing loss reported in this study was low compared to that reported by Dokal 15 and Shimamura et al 1 Routine screening was not carried for financial reasons. Mucosal bleeding was the first and most common presentation in Sudanese children with FA; this is not different from what was reported in the English literature.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Eye dysmorphism was present in half of the patients, a rate higher than that reported by Dokal 15 and Shimamura et al 1 as well as that reported from Korea. 11 The rate of hearing loss reported in this study was low compared to that reported by Dokal 15 and Shimamura et al 1 Routine screening was not carried for financial reasons. Mucosal bleeding was the first and most common presentation in Sudanese children with FA; this is not different from what was reported in the English literature.…”
Section: Discussioncontrasting
confidence: 58%
“…10 Family history of similar disease and/or blood transfusion was present in one third of the studied population, a rate far higher than that reported from Korea. 11 This in addition to the high rate of consanguinity supported the genetic nature of the disease. The mode of inheritance of FA in this study is probably an autosomal recessive which is the commonest pattern of inheritance in this disease.…”
Section: Discussionmentioning
confidence: 85%
“…al., conducted in India. However, this finding is exceptionally different from studies done in western countries where the median age at diagnosis is 6 years 40 . This difference is indicating the trend of late diagnosis of FA in Southeast Asia.…”
Section: Discussioncontrasting
confidence: 55%
“…This finding is consistent with most other publications 32,37 . Pallor is also a very frequent finding in most studies done worldwide 40 . We also observed pallor in more than 50% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although overall survival has been increased since the advent of hematopoietic stem cells transplant (HSCT), the risk of squamous cell carcinomas (SCC) in the oral cavity, esophagus, and the anogenital region is greatly increased in FA patients, with a much earlier onset …”
Section: Introductionmentioning
confidence: 99%